Characterizing primary atomization of cryogenic LOX/Nitrogen and LOX/Helium sprays by visualizations coupled to Phase Doppler Interferometry. (November 2019) - Fdida, N.; Mauriot, Y.; Vingert, L.; Ristori, A.; Théron, M.
Abstract: There is a need for experimental data in conditions representative injection in rocket engines to validate or initiate droplet formation models used in numerical simulations. A new cryogenic vessel was built upon the MASCOTTE test bench to study the atomization of a single oxygen liquid jet, under non-reactive conditions, with simultaneous optical diagnostics. A test plan was built to explore the fiber-type regime occurring in liquid rocket injection systems, with a fixed Reynolds number and a large range of Weber number and momentum flux ratio, compared to existing studies. High-speed images are used to describe qualitatively the fiber-type regime and to visualize were droplets are present, in order to prepare the drop-size measurements. Phase Doppler Interferometry is used to measure the size and velocity of droplets produced by atomization of a liquid oxygen jet by a co-flowing gas. Droplet size and velocity measurements were performed with a PDI close to the nozzle exit in order to provide data on droplets produced by the primary atomization process, which can be useful for numerical simulations initialisation. The radial evolutions of the axial velocity and of the drop size distribution show similar trends as observed in the literature. The axial velocity is investigated for different operating conditions with helium or nitrogen as atomizing gas, showing an increase on the side of the spray. The radial evolution of the droplet size shows a translation of the drop size distribution on the edge of the spray towards the smaller sizes, indicating that the biggest liquid elements stay close to the LOX jet. Highlights: An experimental study on primary atomization of cryogenic sprays is proposed. Fiber-type atomization regime is investigated in a large Weber number range. PDI is performed to measure drop-size and velocity close to the injector. Drop-size distributions evolve radially towards the small sizes. Axial velocities increase radially with the gaseous Weber number.